2021
DOI: 10.3389/fbioe.2020.637397
|View full text |Cite
|
Sign up to set email alerts
|

Co-production of Xylooligosaccharides and Xylose From Poplar Sawdust by Recombinant Endo-1,4-β-Xylanase and β-Xylosidase Mixture Hydrolysis

Abstract: As is well-known, endo-1,4-β-xylanase and β-xylosidase are the rate-limiting enzymes in the degradation of xylan (the major hemicellulosic component), main functions of which are cleavaging xylan to release xylooligosaccharides (XOS) and xylose that these two compounds have important application value in fuel, food, and other industries. This study focuses on enzymatic hydrolysis of poplar sawdust xylan for production of XOS and xylose by a GH11 endo-1,4-β-xylanase MxynB-8 and a GH39 β-xylosidase Xln-DT. MxynB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Homology modeling indicated that the three-dimensional structural model of the catalytic domain (XynA-Tr) displays a typical GH10 family protein structure. GH10 family xylanase is one of the most employed xylanases for XOS production due to their high substrate specificity, efficiency, and yield of XOS [ 16 , 17 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Homology modeling indicated that the three-dimensional structural model of the catalytic domain (XynA-Tr) displays a typical GH10 family protein structure. GH10 family xylanase is one of the most employed xylanases for XOS production due to their high substrate specificity, efficiency, and yield of XOS [ 16 , 17 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, in the combined reactions, the amount of X2 and X3 remarkably decreased compared to the degradation products obtained using Xyl11 individually ( Figure 5A ). Compared with the major degradation product (4.28% X1 at 10 h) obtained using commercial β-xylosidase alone, employing Xyl11 together with it leaded to the X1 yield from enzymatic hydrolysis of beechwood xylan was dramatically increased by 78.84% ( Figure 5B ), which was comparable with that of Dictyoglomus thermophilum β-xylosidase and Aspergillus niger NL-1 xylanase in the sequential hydrolysis reaction (xylose yield of 89.9%) ( Li et al, 2021 ); this indicated synergism effects between Xyl11 and commercial β-xylosidase during the degradation process, in which xylan was converted into XOSs (X2 and X3) by the action of Xyl11 and further effectively cleaved into X1 by commercial β-xylosidase. In addition, it is noteworthy that the synergy degree of beechwood xylan by Xyl11 and commercial β-xylosidase degradation was 15.02, which was slightly higher than or comparable with other reported values ( Cintra et al, 2017 ; Liu et al, 2019 ).…”
Section: Resultsmentioning
confidence: 81%
“…It showed maximal activity toward beechwood xylan (121.99 ± 5.66 U/ml), followed by wheat arabinoxylan (33.14 ± 3.02 U/ml). However, it had no activity toward CMC-Na, suggesting that Xyl11 is not efficient at cellulose degradation, similar to the endo-β-1,4xylanases of Penicillium citrinum HZN13 (Bagewadi et al, 2016), B. subtilis Lucky9 (Chang et al, 2017), P. barengoltzii CAU904 (Liu et al, 2018), and A. niger NL-1 (Li et al, 2021). Cellulase-free β-xylanases can degrade hemicellulose selectively with minimal cellulose loss; they are hence beneficial for industrial applications, such as in the pulp bleaching and food industry (Belfaquih et al, 2002).…”
Section: Substrate Specificity and Kinetic Parameters Of Xyl11mentioning
confidence: 99%
“…However, the strains P. distincta ATCC 700518 T , KMM 3548, 16-SW-7, and U2A are enriched in endo-1,4-β-xylanases and β-xylosidases of the families GH1, 3, 5, 8, 10, and 43 [ 47 ], suggesting an efficient utilization of hemicellulose in plants and algae, while the GHs 8, 10, and 43 are absent in the strains TAE79 and 80 ( Figure 8 ). The strain P. distincta U2A is expectedly equipped with additional hydrolases capable of algal poly- and oligosaccharide degradation, such as GH110 (alpha-galactosidase) and GH150 (Ι-carrageenase) [ 5 ].…”
Section: Resultsmentioning
confidence: 99%